Oxidative stress induced by epileptic seizure and its attenuation by melatonin - Mareš, Jiří; Stopka, Pavel; Nohejlová, Kateryna; Rokyta, Richard (Physiological research, 2013)
An epileptic seizure and postictal period in addition to well-known features are also characterized by massive consumption of energy. This is thought to lead to oxidative stress and increased generation of free radicals, which is reflected by increased levels of oxidative products. Our previous work described the neuroprotective effects of melatonin in preventing cognitive worsening after a single epileptic seizure. This work was aimed on direct measurement of free radicals in brain tissue using the EPR method 1, 15 and 60 minutes after seizure. The measurement was performed in adult male Wistar rats at the mentioned intervals after a single tonic-clonic seizure induced by flurothyl. In comparison to control animals there was a significant increase in hydroxyl and nitroxyl radicals 60 minutes after the seizure. The levels of hydroxyl radicals were significantly lower in animals that received melatonin 60 minutes before seizure induction compared to animals without preventive treatment. Therefore, melatonin affected the generation of the measured free radicals differently. An important finding was the delayed increase in free radicals after a single seizure in the later phases of recovery.
Keywords: látky tlumící činnost CNS; melatonin; antioxidancia; Nitrogen Oxides; Melatonin; zvířata; Rats; Antioxidants; oxidační stres; hydroxylový radikál; mužské pohlaví; Reactive Oxygen Species; Epilepsy; Oxidative Stress; Rats, Wistar; reaktivní formy kyslíku; krysa rodu Rattus; potkani Wistar; epilepsie; Animals; oxidy dusíku; Central Nervous System Depressants; Hydroxyl Radical; Male